Multiclass Classification of fMRI using Linear Collaborative Discriminant Regression Classifier - Gupta, KO; Chatur, PN (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a hybrid GA-LCDRC model is proposed to address multiclass functional MRI classification problem. KNN based genetic algorithm is used as the feature selector and linear collaborative discriminant regression classifier (LCDRC) is used as the classifier. The effectiveness and usefulness of this model is assessed based on its classification specificity, sensitivity and accuracy. This approach is tested to Haxby’s 2001 functional MRI dataset with eight different classes. The result indicates that the proposed hybrid model can be used for multiclass cognitive state classification.